Applying the Lifestyle Routine Activities Theory to Understand Physical and Nonphysical Peer Victimization. Issue 3 (16th March 2017) - Cho, Sujung; Hong, Jun Sung; Espelage, Dorothy L.; Choi, Kyung-Shick
ABSTRACT: Peer victimization is a serious problem, and understanding where, with whom, and how long victims spend their time is important. Applying the lifestyle routine activities theory (LRAT), this study examines the association between 4 components of LRAT and physical and nonphysical peer victimization. Using the 2007 National Crime Victimization Survey, we examined Poisson and negative binomial regression models to explain whether physical and nonphysical peer victimization was affected by measures of routine activities. Our findings indicate that students' exposure and proximity to motivated offenders, school environment, capable guardianship, and target attractiveness were associated with risk of peer victimization. Findings also reveal that risk factors varied depending on the type of victimization.